2017
DOI: 10.5014/ajot.2018.028431
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Occupational Therapy Using Ayres Sensory Integration®: A Systematic Review

Abstract: This systematic review addresses the question "What is the efficacy of occupational therapy using Ayres Sensory Integration (ASI) to support functioning and participation as defined by the International Classification of Functioning, Disability and Health for persons with challenges in processing and integrating sensory information that interfere with everyday life participation?" Three randomized controlled trials, 1 retroactive analysis, and 1 single-subject ABA design published from 2007 to 2015, all of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
84
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 46 publications
4
84
0
12
Order By: Relevance
“…From this, 136 intervention outcome indicators were identified, whereby an intervention, with an individual target outcome was administered to specific diagnostic groups. Insufficient data was available for Schaaf, Dumont, Arbesman & May-Benson, 2018;Smith et al, 2014;Snider, Majnemer & Darsaklis, 2010;Storebø et al, 2011;Tatla et al, 2013;Tatla, Sauve, Jarus, Virji-Babul & Holsti, 2014;Vargas & Lucker, 2016;Westendorp et al, 2014;Whalen & Case-Smith, 2012;Xu, He, Mai, Yan & Chen, 2015;Zadnikar & Kastrin, 2011;Ziviani, Feeney, Rodger & Watter, 2010;Zwicker & Mayson, 2010); 10% (n = 14/130) were graded 'probably don't do it' (Yellow Measure) (Wallen & Gillies, 2006;Wells, Marquez & Wakely, 2018); and 4% (n = 6/135) were graded 'don't do it' (Red Stop) (Gringras et al, 2014;Katalinic et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…From this, 136 intervention outcome indicators were identified, whereby an intervention, with an individual target outcome was administered to specific diagnostic groups. Insufficient data was available for Schaaf, Dumont, Arbesman & May-Benson, 2018;Smith et al, 2014;Snider, Majnemer & Darsaklis, 2010;Storebø et al, 2011;Tatla et al, 2013;Tatla, Sauve, Jarus, Virji-Babul & Holsti, 2014;Vargas & Lucker, 2016;Westendorp et al, 2014;Whalen & Case-Smith, 2012;Xu, He, Mai, Yan & Chen, 2015;Zadnikar & Kastrin, 2011;Ziviani, Feeney, Rodger & Watter, 2010;Zwicker & Mayson, 2010); 10% (n = 14/130) were graded 'probably don't do it' (Yellow Measure) (Wallen & Gillies, 2006;Wells, Marquez & Wakely, 2018); and 4% (n = 6/135) were graded 'don't do it' (Red Stop) (Gringras et al, 2014;Katalinic et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the physical and psychological impairments, including sensory processing difficulty, make cooperation and tolerance to dental treatment even more difficult for children with DD. Sensory‐based interventions and sensory integration therapy have been used in occupational therapy to improve children's functions of daily life and to develop adaptive responses to the child's sensory processing and motor planning skills . A systematic review on sensory‐based interventions concluded that there is limited evidence to support the use of sensory‐based interventions on improving behavior in children.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory-based interventions and sensory integration therapy have been used in occupational therapy to improve children's functions of daily life and to develop adaptive responses to the child's sensory processing and motor planning skills. 21,31,32 A systematic review on sensory-based interventions concluded that there is limited evidence to support the use of sensory-based interventions on improving behavior in children. However, these studies often used a single-sensory strategy (eg, a weighted vest) or they did not follow specific protocols.…”
Section: Discussionmentioning
confidence: 99%
“…First, SI is defined incorrectly here as including sensory diets, brushing and weighted vests. Recent systematic reviews have highlighted the importance of correctly defining SI using a specific fidelity measure (Schaaf, Dumont, Arbesman, & May-Benson, 2018;Schoen et al, 2019). A correct definition is an important first step in evaluating the evidence of interventions.…”
mentioning
confidence: 99%
“…Novak and Honan have included a number of studies in their systematic review, which claim to evaluate SI, but do not meet the fidelity criteria and are therefore not SI.Our second concern is that Novak and Honan (2019) appear to have conflated the research evidence for children from different disabilities, for example, autism and cerebral palsy, in relation to sensory interventions and this is problematic. Recent systematic reviews demonstrate effectiveness of SI for children with autism in relation to functional and participation outcomes, provided specific fidelity criteria were met (Schaaf et al, 2018;Schoen et al, 2019). Novak and Honan appear to have conflated SI and Bobath citing an editorial (Mayston, 2016) which is relevant to Bobath for children with cerebral palsy, not SI for children with autism, without reference to updated SI fidelity literature.…”
mentioning
confidence: 99%